PENGARUH STRUKTUR ASET, PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mahendra Alif Kurniawan, 13.05.52.0163; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
This study examines the effect of asset structure, profitability, liquidity, firm size and growth sales. This study uses data of property and real estate companies listed in Indonesia Stock Exchange (IDX). The sampling method in this research used purposive sampling with the observation period from 2014 to 2016. The data is processed as many as 84 companies. The data collected then in if with statistical tools that IBM SPSS Statistic 22.0 and analysis tools is a multiple regression analysis method. The results showed that firm size had a positive effect on capital structure; liquidity had a negative effect on capital structure; asset structure, profitability, growth saleshad no effect on capital structure.Keyword: Asset Growth, Firm Size, Profitability, Asset Structure, Firm Age, Cash Holding, Liquidity and Capital Structure.